The day the sun rose in the west : Bikini, the Lucky Dragon, and I - Ōishi, Matashichi (University of Hawaiʻi Press, 2011)
A translation of Bikini jiken no shinjitsu, expanded by excerpts from Bikini jiken no omote to ure, and shortened by deletions especially from Chapter 4.